Sifat Mutu Sensori dan Kimia Selai Kulit Buah Naga Merah dan Buah Sirsak - Ellyvia Primaviera; Intan Kusumaningrum; Titi Rohmayanti, S.Si, M.Si (Universitas Djuanda, 2024)
Jam is a semi-solid food product made from fruit and sugar. This study aims to utilize red dragon fruit skin and soursop fruit flesh as jam. This study used a one-factor Completely Randomized Design (CRD) with a ratio of red dragon fruit skin pulp and soursop fruit pulp at five treatment levels, namely 20%:80%, 35%:65%, 50%:50%, 65%:35%, and 80%:20% with two repetitions. Product analysis consists of chemical tests for water content, ash content, crude fiber, total dissolved solids, degree of acidity (pH), sensory quality test, and hedonic test to determine the selected product. The analysis of research data used a test of variance (ANOVA) with Duncan's advanced test. The results of the research on selected products in the treatment of 80% red dragon fruit skin pulp: 20% soursop fruit pulp, which has a moisture content of 33.33%, an ash content of 0.49%, 3.45% crude fiber, and 50.10% total dissolved solids. Sensory quality tests lead to a purplish red color, smells of red dragon fruit skin, smells of soursop fruit, sweet and not sour taste, a non-bitter aftertaste, a soft mouth texture, easy to spread, and hedonic test on all parameters leads to likes.